Sepsis Triggers a Late Expansion of Functionally Impaired Tissue-Vascular Inflammatory Monocytes During Clinical Recovery - Baudesson de Chanville, Camille; Chousterman, Benjamin Glenn; Hamon, Pauline; Laviron, Marie; Guillou, Noelline; Loyher, Pierre Louis; Meghraoui-Kheddar, Aida; Barthelemy, Sandrine; Deterre, Philippe; Boissonnas, Alexandre; Combadière, Christophe (Frontiers in Immunology, 2020)
Sepsis is characterized by a systemic inflammation that can cause an immune dysfunction, for which the underlying mechanisms are unclear. We investigated the impact of cecal ligature and puncture (CLP)-mediated polymicrobial sepsis on monocyte (Mo) mobilization and functions. Our results show that CLP led to two consecutive phases of Mo deployment. The first one occurred only few days after the induction of the peritonitis while the second phase was of larger amplitude and extended long after the apparent clinical recovery. The latter was associated with the expansion of Mo in the tissue reservoirs (bone marrow and spleen), their release in the blood and their accumulation in the vasculature of peripheral non-lymphoid tissues. It occurred independently of the infectious status but relied on inflammatory-dependent pathways and coincided with increased susceptibility and severity to a secondary infection. The intravascular lung Mo displayed limited activation capacity, impaired phagocytic functions and failed to transfer efficient protection against a secondary infection into monocytopenic CCR2-deficient mice. In conclusion, our work unveiled key dysfunctions of intravascular inflammatory Mo during the recovery phase of sepsis and provided new insights to improve patient protection against secondary infections.